2018
DOI: 10.1038/s41598-018-27628-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular chaperoning helps safeguarding mitochondrial integrity and motor functions in the Sahara silver ant Cataglyphis bombycina

Abstract: The Sahara silver ant Cataglyphis bombycina is one of the world’s most thermotolerant animals. Workers forage for heat-stricken arthropods during the hottest part of the day, when temperatures exceed 50 °C. However, the physiological adaptations needed to cope with such harsh conditions remain poorly studied in this desert species. Using transcriptomics, we screened for the most heat-responsive transcripts of C. bombycina with aim to better characterize the molecular mechanisms involved with macromolecular sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…the number of genes that are differentially expressed) differences in responses to environmental pressures in a variety of organisms, including plants, insects, molluscs, crustaceans, and fish (Ye et al ., 2014; Zhao et al ., 2014; Cañas et al ., 2015; Faddeeva et al ., 2015; Cheng, Hui, & Sha, 2019; Jesus et al ., 2019). In recent years, DGE studies in social insects have highlighted a number of genes that are involved in colony organisation and adaptation to environmental constraints (Ferreira et al ., 2013; Helmkampf et al ., 2016; Lucas, Romiguier, & Keller, 2017; Willot et al ., 2018; Holman et al ., 2019). However, such studies remain fairly rare, and many taxa are currently ignored.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…the number of genes that are differentially expressed) differences in responses to environmental pressures in a variety of organisms, including plants, insects, molluscs, crustaceans, and fish (Ye et al ., 2014; Zhao et al ., 2014; Cañas et al ., 2015; Faddeeva et al ., 2015; Cheng, Hui, & Sha, 2019; Jesus et al ., 2019). In recent years, DGE studies in social insects have highlighted a number of genes that are involved in colony organisation and adaptation to environmental constraints (Ferreira et al ., 2013; Helmkampf et al ., 2016; Lucas, Romiguier, & Keller, 2017; Willot et al ., 2018; Holman et al ., 2019). However, such studies remain fairly rare, and many taxa are currently ignored.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Consistent with this finding, workers of a thermophilic seed‐harvester ant species ( Pogonomyrmex barbatus ) displayed greater constitutive expression and induction of hsp genes ( hsp83 , hsc70‐4 h1 , hsc70‐4 h2 , and hsp 40 ) in response to heat stress, compared to workers of a species found in more mesic habitats ( Aphaenogaster picea ) (Nguyen, Gotelli, & Cahan, 2016; Stanton‐Geddes et al ., 2016). In a study comparing Cataglyphis ants, constitutive expression of hsp70 was found to be correlated with local thermal conditions (Willot, Gueydan, & Aron, 2017; Willot et al ., 2018). Workers of the Saharan silver ant ( C. bombycina ) had high constitutive levels of Hsp70, even when they were in the nest, where the temperature was around 25°C (Gehring & Wehner, 1995; Willot, Gueydan, & Aron, 2017).…”
Section: Physiological and Molecular Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then ran two tests with these normalized data: (1) heat stressed ants (35˚C) versus control ants (21˚C) and (2) cold stressed ants (5˚C) versus control ants (21˚C). Transcripts were considered to be differentially expressed (DE) if i) the Benjamini and Hochberg adjusted false discovery rate (FDR) p-value was less than 0.01, ii) the absolute value of the fold-change (FC) � 2.0, and iii) the relative standard deviation (RSD) of expression between replicates was less than 0.4 [31].…”
Section: Differential Gene Expression Analysismentioning
confidence: 99%
“…There are very few studies of ants that have attempted to identify genes and pathways associated with a cold or hot stress response without a priori information. One recent study looked at gene expression in Cataglyphis bombycina during heat stress and documented induction of molecular chaperones [31]. However, we are unaware of studies that have documented genes induced during hot and cold stress in an ant with a preference for cold.…”
Section: Introductionmentioning
confidence: 99%